Desquamative interstitial pneumonitis in a patient with systemic lupus erythematosus. - Esmaeilbeigi, F; Juvet, S; Hwang, D; Mittoo, S (2012)
Desquamative interstitial pneumonia (DIP) is a rare form of interstitial lung disease (ILD) commonly found among healthy smokers. ILD is a rare manifestation of systemic lupus erythematosus (SLE), and typically associated with a histopathological pattern of nonspecific interstitial pneumonia (NSIP). The present article describes an unusual case of DIP in a nonsmoking patient with SLE presenting as NSIP. DIP can occur in the context of SLE in patients with a negative smoking history, and clinicians should consider lung biopsy to correctly classify ILD with unusual presentation on computed tomography scan.